Observations and recommendations regarding ethnoeducation in Colombia - Balán, Laura (Frontiers in Education, 2025)
This policy brief examines the challenges and opportunities of ethnoeducation in Colombia, highlighting persistent structural inequalities affecting Indigenous and Afro-Colombian communities. Drawing on critical interculturality, the analysis reveals how current policies often essentialize ethnicity, reproduce educational segregation, and limit genuine dialogue. While acknowledging advances in access and cultural affirmation, the brief critiques the separation of curricula and the exclusion of the dominant society from intercultural education. It proposes systemic reform based on intercultural learning for all, teacher training in minoritized knowledges, community-based curriculum design, and better data systems. Emphasis is placed on decolonizing education to dismantle racial hierarchies and foster mutual learning. The brief concludes with a phased roadmap for reform, recognizing political resistance while positioning interculturality as a shared national responsibility.